Pengaruh Profitabilitas, Likuiditas Dan Ukuran Perusahaan Terhadap Kebijakan Dividen - Nindya Pangestika Pratiwi; Eny Purwaningsih (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The company's decision to distribute dividends is an important decision, because it can affect investors in investing their capital into the company. This research aims to inform companies empirically and partially or simultaneously about profitability, liquidity and company size on dividend policy in companies that are members of the 2020 high dividend index for the period 2018-2020. The causal relationship of two or more variables can be determined by using comparative causality. Obtained 10 companies that match the criteria of the research sample using purposive sampling method. Thus, 30 samples of financial statements were obtained for companies in the 2020 high dividend index for the period 2018-2020. This research method uses multiple regression analysis. The results of this research show that the variables of profitability (ROA), liquidity (CR) and company size (FS) partially have a positive and significant effect on policy. dividends (DPR). And simultaneously profitability, liquidity and firm size affect dividend policy.